PROTECTION OF THE ENVIRONMENT DURING ARMED CONFLICTS: ECONOMIC AND INTERNATIONAL LEGAL ASPECTS - Liudmyla Golovko; Viktor Ladychenko; Olena Yara (Baltic Journal of Economic Studies)
The environment is one of the casualties of armed conflict. In the context of military operations, a range of ecological impacts is observed, including but not limited to: human casualties; destruction of infrastructure; pollution of air, land and water resources; and damage to forests and nature reserves. Moreover, as military technologies develop, the situation is only getting worse. Environmental damage also has far-reaching economic consequences. All of this suggests that there is a need for high-quality international legal regulation of environmental protection during armed conflicts. The purpose of this article is twofold: firstly, to analyse the consequences of environmental damage caused by the Russian Federation's aggression for the Ukrainian economy; and secondly, to identify the existing international legal regulation of environmental protection during armed conflict. In addition, the article will propose ways to solve the identified problems. An analysis was conducted on statistical data pertaining to the environmental damage caused by various armed conflicts. The issue of international legal regulation of the assessment of damage caused to the environment during military conflicts was considered. Methodology. In the course of composing the article, the primary focus was on the utilisation of general theoretical methodologies. The analysis and synthesis of existing literature, alongside theoretical generalisation and systematic interpretation, were instrumental in evaluating individual international treaties pertinent to the research topic. Results. The article considered the economic consequences of environmental damage caused by the Russian Federation in Ukraine, as well as the content of international legal regulations on environmental protection during armed conflicts and the practice of implementing them. Practical implications. The authors have identified the main range of problems existing in the sphere of international legal regulation of environmental protection, and proposed the possible ways of their resolving, on the basis of doctrinal provisions, data from reports of the Ministry of Environment and Natural Resources of Ukraine and the UN, as well as the norms of the current international law. Value/Originality. It has been determined that a significant step in enhancing the international legal regulation of environmental protection during armed conflict is necessary. This step involves the enactment of a separate convention aimed at resolving this issue, as well as the adoption of international standards on environmental damage assessment.